112k views
3 votes
11. f(x) = x + 3, g(x) = -x + 2. Find (f + g)(x)

1 Answer

4 votes

Answer:

(f + g)(x) = 5

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Terms/Coefficients
  • Functions
  • Function Notation

Explanation:

Step 1: Define

Identify

f(x) = x + 3

g(x) = -x + 2

(f + g)(x) is f(x) + g(x)

Step 2: Find

  1. Substitute in function values: (f + g)(x) = x + 3 - x + 2
  2. [Subtraction] Combine like terms (x): (f + g)(x) = 3 + 2
  3. Add: (f + g)(x) = 5
User FelisCatus
by
4.5k points